Molecular detection of Candidatus Ehrlichia pampeana (Rickettsiales: Anaplasmataceae) in Haemaphysalis juxtakochi (Acari: Ixodidae) from central Argentina - Flores, Fernando Sebastian; Sebastian, Patrick Stephan; Nava, Santiago (Springer, 2024)
The aim of this study was to report the first detection of Candidatus Ehrlichia pampeana in Haemaphysalis juxtakochi from Argentina. Free-living ticks were collected from vegetation by drag-flag method on five sample sites in Entre Ríos Province, central Argentina, belonging to the Espinal Phytogeographic Province. Molecular detection of order Rickettsiales agents was performed using gltA (Rickettsia spp.), 16 S rRNA and groEL (Anaplasmataceae) genes as targets. A total of 67 ticks of Amblyomma aureolatum (20 nymphs and 4 adults), Amblyomma dubitatum (15 nymphs) and Haemaphysalis juxtakochi (24 nymphs and 4 adults) were collected. While all tested ticks were negative for Rickettsia spp., and Anaplasmataceae agents could neither be detected in A. aureolatum nor in A. dubitatum, Candidatus Ehrlichia pampeana was detected in one male of H. juxtakochi. DNA sequences of this microorganism (16 S rDNA and groEL) are related to sequences of Ehrlichia ewingii. The findings of the current study represent the first report of this Ehrlichia strain for Argentina.